(untitled) (Economic and Political Thought, 2017)
Today, EU and China – along the US – undoubtedly play a key role in the international arena. They have established strategic partnership in their bilateral relations and strive to develop cooperation in all areas. Yet, they also dissent on many important issues. In this article, I investigate the premises of EU-China bilateral relations, as well as opportunities and threats to both parties as far as their status on the global stage is concerned. Moreover, I test the thesis I deem controversial, which claims that the twenty-first century will be Asian century, and de facto the era of China. The literature on contemporary China, on the role it plays in the international arena and on its relations with the EU is abundant. However no definite answer has been given yet as to where China is heading and whether the EU will break up in the twenty-first century. China’s ‘turn to multilateralism’ is questioned, with some researchers claiming that it simply serves to conceal China’s long-term goal, i.e. taking control over the world in the second half of the twenty-first century.